Analysis Of Regional Property Management According To Government Regulation Number 27 OF 2014 In The Government Of Meranti Islands - Husnul Muttaqin (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This research aims to determine the implementation of regional properties management according to The Government Rule Number 27 in 2014 and find out what causes the problems of management of regional property in Meranti Islands Regency. This reserch is qualitative research using the Soft System Methodology approach, which explores real life with a limited system through collecting data in the form of interviews with twelve participants, observing and from documents or report.The results of the study show that Meranti Islands Regency does not implement the Government Rule Number 27 in 2014 thoroughly yet, and the problem is because The Standard Operating Procedure (SOP) is not done and renewed yet in accordance with The Government Rule Number 27 in 2014. Beside that, the results of this study also show that there is weakness and deficiency on the human resources and not yet obedient towards the valid rules.In order to overcome the problems, this research recommends to The Government of Meranti Islands Regency to arrange Standard Operating Procedure (SOP) in line with the law and in the case of managing regional properties, give education, and training, to the human resources involved in the management of regional properties and conducting activities related to the management of regional properties in accordance with law and regulations.